Evaluation of the microenvironment formed by interferon-β - Yamagishi, Mai; Hori, Yutaka; Suzuki, Nobutake; Peng, Yu; Harada, Yoshie; Funatsu, Takashi; Ohara, Osamu; Shirasaki, Yoshitaka (Frontiers in Chemical Biology, 2025)
Heterogeneity in the cellular microenvironment in vivo affects the variability of reactivity among immune cells. Individual-specific microenvironmental differences play a crucial role in determining macroscopic outcomes, such as the efficacy of immunotherapy and disease progression. The microenvironment is also featured by cytokines released from cells, significantly regulating immune cell function. However, the overall understanding, at single-cell resolution, of how cytokines shape the microenvironment and promote paracrine signaling remains unclear. In this manuscript, we propose a methodology that addresses both the microenvironment itself and the response to the microenvironment to comprehend microenvironment behavior at the single-cell level. Our objective is to contribute to the basic understanding of the interplay between immune cells and their microenvironment, with particular relevance to implications for immunotherapy and disease progression.